Improving policy coherence for circular cities - Felipe Bucci Ancapi (A+BE: Architecture and the Built Environment)
This dissertation develops an understanding of circular built environment policies. It draws of Jo Williams’ Circular City Development and Måns Nilsson et al. Policy Coherence analysis Framework to propose a framework for ex ante circular city policy coherence analysis, which is developed and tested through three case studies: campus development at TU Delft (Netherlands), circular built environment policy in Greater London (UK), and mass timber construction policy in Amsterdam (Netherlands). The dissertation uncovers policy formulation by means of circular economy policy objectives, instruments and implementation practices. It shows that in the selected case studies, circular economy policies are increasing their coherence by means of supply chain and business driven circular economy frameworks, but less so in developing circular urban systems. Currently, the circular built environment policies analysed throughout this dissertation are based on looping actions (e.g., recovery, recycling, reusing) and tend to overlook ecological regeneration actions (e.g. blue and green infrastructure and urban ecosystem services provision) and adaptation actions (e.g. community-led co-creation and capacity building). Ultimately, this dissertation argues that current circular built environment policies ‘cannot see the city for the buildings’ and that ex ante evaluation of circular city policies can contribute to improve the alignment and synergies between policy objectives, instruments and implementation practices towards circular city development.